Green Synthesis of Heterocyclic Compounds Using Eco-Friendly Catalysts (The International Journal for Scientific Research, 2026)
This study investigates the green methods of making heterocyclic compounds with safe catalysts. Results are analyzed using data-driven techniques to assess their efficiency, spectral authenticity and activity towards living organisms. For this study, a set of 1000 heterocycles was made using experimental values from the literature for reaction yield, melting point, NMR, IR, UV-V is spectra and both antioxidant and antimicrobial properties. The investigation of interactions between synthetic and functional properties was made possible by the application of descriptive analytics, Pearson correlation, Principal Component Analysis (PCA), KMeans clustering and hypothesis testing. Most of the developed compounds showed a high yield (85–95%) and could withstand heat (melting point 200–250°C), in addition to showing effective antioxidant (80–95%) and antibacterial (20–25 mm inhibition zone) qualities. The study's calculations matched the spectra expected for actual compounds containing aromatic and conjugated groups. Significantly, using statistics revealed no conflict between drug effectiveness and drug production which means pharmaceutical goals can be met with green chemistry. The study shows a repeatable method that can be used outside a lab, where cheminformatics, spectral modeling and statistical learning are incorporated to support green synthesis and preserve bioactivity. It allows the use of a flexible system to test, group and improve the use of heterocycles for sustainable pharmaceutical chemistry.
Keywords: Green Chemistry; Heterocyclic Compounds; Eco-Friendly Catalysts; PCA; Antioxidant Activity